Demographic and Renal Histopathological Profile of Rapidly Progressive Glomerulonephritis in Children - Hasnat, Mohammad Abu; Afroz, Shireen (Journal of Rangpur Medical College, 2026)
Background: Rapidly progressive glomerulonephritis (RPGN) is an uncommon but severe pediatric renal disorder, and its incidence and etiological patterns remain poorly defined. Objective: This study examined demographic features and renal histopathology among affected children. Methods: A prospective observational study was conducted in the Department of Paediatric Nephrology, BICH and Dhaka Shishu Hospital from July 2018 to June 2020, enrolling 28 pediatric cases displaying features of rapidly progressive glomerulonephritisthrough non-probability sampling. Results: The mean age was 9.1±1.9 years in children with more than 50% crescents and 8.7±2.2 years in those with fewer crescents. Males predominated in the high-crescent group, and most participants (82%) were from rural areas. Increased cellularity, mesangial expansion, and interstitial inflammation were frequent in both histological categories. Most children presented with acute kidney injury stage 3, with no significant difference between groups. Conclusion: RPGN in children appears to predominantly affect rural male patients in late childhood, with severe renal dysfunction and similar histopathological patterns across crescentic categories. J Rang Med Col.2026 Mar;11(1): 119-123